You have the following system of equations:
y = -1/2 x + 4 1/2
2 = y - 2x
In order to find the value of x of the previous system, proceed as follow:
- Solve the second equation for y:
y = 2x + 2
- Replace the previous expression for y into the first equation and solve for x:
![\begin{gathered} 2x+2=-(1)/(2)x+4(1)/(2) \\ 2x+2=-(1)/(2)x+(9)/(2) \\ 2x+(1)/(2)x=(9)/(2)-2 \\ (5)/(2)x=(5)/(2) \\ x=1 \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/a5wgzg135scxds46vmzc4dcrr5bl87fenp.png)
Hence, the value of x is x = 1